2020
DOI: 10.21203/rs.3.rs-64755/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of the BATT score for prehospital risk stratification of traumatic haemorrhagic death: Usefulness for tranexamic acid treatment criteria.

Abstract: Background: Tranexamic acid reduces surgical blood loss and reduces deaths from bleeding in trauma patients. Tranexamic acid must be given urgently, preferably by paramedics at the scene of the injury or in the ambulance. We developed a simple score (Bleeding Audit Triage Trauma score) to predict death from bleeding.Methods: We conducted an external validation of the BATT score using data from the UK Trauma Audit Research Network (TARN) from 1st January 2017 to 31st December 2018. We evaluated the impact of tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…14 The BATT score was externally validated in the TARN registry. 15 The score includes variables used for initial assessment (vital signs, level of consciousness, mechanism of injury, and age) that are available at the scene of injury. Although the predominant injury mechanisms are different in women and men, we did not control for mechanism of injury as it is already included in the BATT score and this could lead to over-adjustment bias (Supplementary Appendix 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 The BATT score was externally validated in the TARN registry. 15 The score includes variables used for initial assessment (vital signs, level of consciousness, mechanism of injury, and age) that are available at the scene of injury. Although the predominant injury mechanisms are different in women and men, we did not control for mechanism of injury as it is already included in the BATT score and this could lead to over-adjustment bias (Supplementary Appendix 1).…”
Section: Discussionmentioning
confidence: 99%
“…The strengths and weaknesses of the BATT score are discussed in the external validation study. 15 The TARN registry had missing values for prehospital physiological variables, for time of injury, and for receipt of TXA. For this reason, we imputed missing values, assuming that they were missing at random.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presenting vitals/labsShock index - (HR/SBP > 0.8) an independent predictor of transfusion and mortality 94 .HISS score uses presenting labs of glucose, lactate, pH, potassium, pO2 to predict mortality and ICU stay 97 .Overall injury burden/injury severity scoreDisplaced pelvic fracture, positive FAST, increased ISS → increased risk of needing massive transfusion 102 .BATT score to predict hemorrhagic death: age, GCS, mechanism of injury, vital signs 98 . The prediction of acute coagulopathy of trauma (PACT) score used similar variables 93 .Mechanism of injuryBlunt trauma with shock associated with increased risk of bleeding.…”
Section: - What Is the Best Way To Determine Acute Blood Loss And Pre...mentioning
confidence: 99%
“…However, Schroll et al, found ABC score to have lower sensitivity but greater specificity than shock index for predicting massive transfusion 101 . Further systems include the bleeding audit for trauma & triage (BATT) score, developed to predict hemorrhagic death in trauma, which uses SBP < 100, BP > 100, as well as respiratory rate, the Glasgow coma scale (GCS) score, age, penetrating mechanism, and high velocity trauma 98 . The head injury severity score (HISS) uses presenting labs of glucose, lactate, pH, potassium, and pO 2 to predict mortality and intensive care unit (ICU) stay 97 .…”
mentioning
confidence: 99%